Modificación del aporte de energía y de nutrientes en la dieta de embarazadas que participaron en un programa de complementación y suplementación alimentaria (2008)
ABSTRACT: To compare changes in nutrients and energy intake of seventy seven pregnant women who participated in a nutritional intervention program in Cauca and Uraba-Antioquia, Colombia. Methodology: Descriptive longitudinal and prospective study was conducted in seventy seven pregnant women during the first trimester; surveys questioned the pregnant women and included 24-hour recall (personal interview) in two different days. Mothers started to participate of the nutritional intervention program that included a complement, a sub complement and additional nutritional education was provided. Energy and nutrients intake was assessed again in the last two trimesters of pregnancy. The PC_SIDE program (Iowa state University) was applied to identify the amount of energy and nutrients consumption by mothers as well as to identify the prevalence of nutrient deficiencies. Data were adjusted and variance analysis was used. Significant of p<0.5 were considered. Results: A statistically significant increased in nutrients intake, and prevalence of deficiency risk was reduced in this study. Even though, risk of malnutrition is still high, because of the precarious economical conditions in this population. Conclusion: Complementary food program contributed to improve energy and nutrients intake by pregnant women, because of there was no changes and interventions on social economical conditions we conclude that nutritional intervention programs help to improve nutritional status for this specific population.